Effect of Economic Hardship, Deprivation and Peer Influence on Street Children in Khartoum, Sudan - Mohammed Ahmed, Najla Abdallah; Shahabudin, Sharifah Muhairah; Singaravelloo, Kuppusamy (Journal of Public Administration and Governance, 2023)
Many children have fled their households to find employment and shelter in Khartoum, Sudan. The absence of the basic needs has forced the children to take to the streets where they feel they have better opportunities to survive in their impoverished state. This situation may have made these children vulnerable to risks such as exposure to vice activities as well as victimisation. One of the ways to survive challenges of the street life is to make friends with other street children and in some instances, the children become part of a larger group or syndicate. To address the challenges faced by street children, the study investigates the influence the street peers may have on the children’s behaviour. A total of 12 marketplaces in Khartoum State and its three municipalities, namely, Khartoum, Omdurman, and North Khartoum (Bahri), were selected in the current study as these localities have large numbers of street children. Using geographical clusters of the areas, followed by a systematic sampling technique, 330 street children were chosen as the sample size of the study. The questionnaire survey was used to obtain data from the respondents, the data collected in 2017. The data analysis tool used SPSS 22. The study reveals that street children in Khartoum take part in varying kinds of maladaptive behaviours and peer influence is found to be the determinant of these behaviours. The study suggests that targeted interventions by social welfare agencies and non-profit organisations should be made to ensure the safety and future of these children.